Menonton Kartun Efektif Menurunkan Nyeri Pemasangan Infus dan Venipuncture pada Anak (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of non-pharmacological therapy of watching cartoons in treating children's pain during infusion and venipuncture. The method used is a systematic review using guidelines from the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). The research results showed ten articles selected after selection and quality assessment using guidance from the JBI critical appraisal tool. Watching videos effectively reduces pain in children during infusion and venipuncture with p